Development of a refractory mold based on chamotte/plaster for jewelry micro-casting with pre-set emeralds - Londoño-Montes, Carlina Sofía; Fernández-Torres, Mayerly Jhojana; Córdoba-Tuta, Elcy María (Universidad Pedagógica y Tecnológica de Colombia, 2017)
During the jewelry stone-in-place micro-casting process, the ceramic mold, which is composed of silica and plaster is stabilized at temperatures close to 650 °C, whereas the casting temperature of the precious metal alloy hovers around 1000 °C. Therefore, this type of micro-casting technique is not suitable for gems such as emeralds, since they are highly susceptible to damage at temperatures over 350 °C. In the face of this fact, the main purpose of the present work is to develop a refractory mold based on chamotte and plaster, which can be stabilized at low temperatures, in order to use it for the micro-casting of pre-set emeralds. To achieve this, the experimental methodology was divided into three phases: i) raw chemical materials, mineralogical, granulometric and thermal characterization; ii) preparation and characterization of chamotte-plaster-water mixtures, including the measurement of casting times, mechanical and microstructural properties, permeability, and resistance to thermal shock; and iii) evaluation of the resulting refractory mold in the micro-casting of pre-set emeralds. The results showed that the refractory mold with composition chamotte/plaster 75/25, an addition of 50 % of water to the dried mixture, and fine granulometry (-200 mesh) had a stabilization temperature of 350 °C. Furthermore, it is possible to subject the emeralds to the stone-in-place micro-casting process that employs the refractory mold developed here, with a thermal treatment that does not surpass the 350 °C, along with a low melting point (398 °C) for the precious metal alloy.